TREATMENT OF HEART FAILURE IN PATIENTS WITH DIABETES MELLITUS - Bilovol, O.M.; Kniazkova, I.I.; Bohun, M.V.; Kuzminova, N.V.; Osovska, N.Y. (World of Medicine and Biology, 2020)
The purpose of the work was to study the effect of fixed combination of meldonium dihydrate and γ-butyrobetaine dihydrate (MD+γ-BD) on clinical, hemodynamic and glucometabolic parameters, as well as indicators of oxidant-antioxidant status in patients (pts) with heart failure (HF) and type 2 diabetes mellitus (DM). The total of 62 patients with HF and DM were examined. After registration of the baseline data, baseline therapy was prescribed to all patients, 30 of them (group 1) obtained an additional fixed combination of MD+γ-BD 2 capsules three times a day for 3 months and 32 patients were included in the comparison group (group 2). After treatment in group 1, the increase of the distance walked was determined according to the 6-minute walk test by 31.2% versus 12.7% in group 2 (p
Keywords: heart failure; type 2 diabetes mellitus; structural and functional changes of the left ventricle; lipid peroxidation; fixed combination of meldonium dihydrate and γ-butyrobetaine dihydrate